KEANEKARAGAMAN JENIS BURUNG DI TAMAN WISATA ALAM WERA - Malau, Santo Doni; Ningsih, Sri; Ihsan, Moh. (Jurnal Warta Rimba, 2015)
Wera a natural park is one of the consevation area in central sulawesi. This research was conduucted in a natural park Wera. This research was a conducted in November 2013 to January 2014. The purpose of this research was to determine the diversity of bird species, composition of bird species, bird attendance rate, evenness index, and dominance of bird species in the natural park Wera. Source of data obtained to collect data bird in a natural park Wera using IPA (point index of abundance). In research used the path length 1000m with a circle whose diameteror radius of a circle of 50m and the distance between midpoint of 100m. Species composition in the morning found 21 bird species included in 15 families with a population of 175 tail. The level of presence of birds in the morning there are 15 kinds of 100%, 50% and 5 types of observations afternoon on 10 kinds of 100%, 6 types of 50%. Diversity index obtained in the morning (H’) 2.819, while in the afternoon diversity index (H’) 2.502, evenness index in a morning (E) 0.941. while in the afternoon (E) 0.902. In the morning there are eleven categories based on guild composition, whereas the composition of forest habitats there are seven categories based guild. Dominance of species of birds on observation that dominant morning there were 45%, 50% sub-dominan, not dominant 5%, while in the afternoon observation that dominant 56%, sub-dominan 44%, which is not dominant is not found. Keywords: bird, diversity, natural park wera